ANALISIS EKOLOGI LANSKAP AGROFORESTRI PADA RIPARIAN SUNGAI CILIWUNG DI KOTA BOGOR - Yulius Budi Prastiyo; . Kaswanto; Hadi Susilo Arifin (http://arl.faperta.ipb.ac.id/, 2017)
Ciliwung River flows from Bogor district, Bogor city, Depok, to Jakarta. The river faces many problems, especially settlement occupation on its riparian zones. The problem has damaged its natural ecological structures and the agroforestry practices such as mixed gardens, forest gardens, and pekarangan (home garden) in riparian landscape. This research objective is to analyze the structure, function, and dynamics of riparian agroforestry landscape of Ciliwung River in Bogor City. The landscape ecological index analysis approach is used to quantify the structure, function, and dynamics of the landscape. The existing land use in Ciliwung riparian in Bogor City has been dominated by the constructed land, such as settlements and housing. Those land use can be found with an area of 33.78 ha (60.50%) in the upper segment and 34.65 ha (56.54%) in the under segment. Meanwhile, in the middle segment is still dominated by the agroforestry area, such as forest gardens, mixed garden, and pekarangan with an area of 17.59 ha (55.23%). The function of these structures is as the core habitat and movement media of material, energy, animal, and human. The spatial dynamics of the Ciliwung riparian landscape in Bogor City revealed that the more patches of settlements and housing on a landscape, the more patches of pekarangan on the landscape.Keywords: Agroforestry landscape, Ciliwung River, landscape ecology, riparian areas